Hantar Sinamo, Charloq*, Rosmayati, Radite - Hantar Sinamo Sinamo; Charloq Charloq; Rosmayati Rosmayati (Jurnal Agroekoteknologi, 2015)
The aim of the research was to evaluate the response of latex production at various times application in multiple clones rubber plant to giving several sources hormone ethylene. The experiment was conducted in October 2013 to March 2014 in Sungei Putih Rubber Research Institute, Galang Subdistrict , Deli Serdang regency. Three-Stage Nested Design was applied with three replications. The first step was time application, i.e., a first application, a second application, a third application, and a fourth application, the second step was clones treatment, i.e., IRR 118 clones, PB 260 clones, IRR 42 clones, IRR 39 clones and the third step was stimulants treatment, i.e., without stimulants, ethrel, SP1, banana peel extract and extract of pineapple skin. Observed parameters was the latex volume. The study showed that time application had no significant increased on latex production, and clones treatment at various times application had no significant to produce on latex production, whereas stimulant treatment in multiple clones at various times application significantly increased latex production. IRR 39 clones were clones that experienced the highest increase in producing due to the provision treatment of stimulants. SP1 was a stimulant that increases the production of the highest latex. Ethrel, banana peel extract was a stimulant that can increase the production of latex higher than without stimulants. Pineapple peel extract resulted in clumping of latex flow on tapping grooves and a low yield of latex productionKeywords: Latex Production, Time Applications, Clones, Stimulants